The Influence of Cognitive Style on Students' Critical Thinking Skills in Physics Material - Hidayatullah, Nisa; Gunada, I Wayan; Susilawati, Susilawati; Zuhdi, Muhammad (AMPLITUDO : Journal of Science and Technology Innovation, 2024)
This research aims to determine the influence of cognitive style on students' critical thinking abilities. This research uses a quasi-experimental method with a factorial design research design. The research subjects consisted of class XI MAN 1 Central Lombok students who were divided into experimental classes and control classes. The experimental class uses the PBL model, while the control class uses a conventional learning model. Research instruments include critical thinking ability tests and the Group Embedded Figures Test (GEFT) cognitive style test. Before the critical thinking ability test instrument is given, a test of the instrument is first carried out, namely a validity and reliability test. level of difficulty, and distinguishing power. The research results show that the significant level value is 0.001 which is smaller than α which is equal to 0.05 (0.000<0.05). These findings indicate that there is an influence of cognitive style on students' critical thinking abilities.